Successful prosecution of intimate violence : making it offender-focused - Ryan, Bridget H.; Valliere, Veronique N. (New York, NY : Routledge, 2023)
"Offender-focused prosecution concentrates attention to the actions, decisions, choices, and motivations of the offender. Crimes of intimate violence tend to compel investigators, prosecutors, and defense attorneys to fixate on the victim's behavior to prove or disprove a case. Prosecutors become helpless faced with uncooperative victims, challenging facts, or attacks on the victims' credibility prosecution can rely on evidence and offender-focused interviewing, investigation, and case construction. This book will offer investigators and prosecutors concrete information and techniques to construct and present offender focused cases in crimes of intimate violence. First we will challenge the reader's biases and assumptions about intimate violence, providing information that will dispel pervasive myths and misinformation we maintain. We will explain the motivations and techniques that offenders use on their victims to ensure the victims' silence, compliance, and resistance to prosecution. The second section will address specific steps that investigators and prosecutors can take for offender-focused prosecution, including interviewing practices, conducting evidence-based investigations, selecting and preparing a jury, and building an offender-focused prosecution through the case. The reader will be offered practical and attainable practices and skills. This book will be primarily intended for investigators or prosecutors. However, it will be accessible to paralegals, victim advocates, judges, and others involved in the criminal justice system to utilize"--
Keywords: Sex offenders; Intimate partner violence; LAW / Family Law / General; SOCIAL SCIENCE / Violence in Society